Malignant Triton Tumour: Case report - V, Sandeep; Kumar, Rajat; K, Smita; Hiremath, S S (Annals of Pathology and Laboratory Medicine, 2019)
Malignant triton tumours (MTTs) are a rare subtype of malignant peripheral nerve sheath tumour (MPNST) showing rhabdomyoblastic differentiation, which have no treatment consensus and a poor prognosis. This case report presents case of a 71yrs/ male with swelling in Right Hand over one month. Patient had same swelling 2yrs back which was diagnosed as Peripheral Nerve Sheath Tumour on histopathology following which he underwent surgery followed by radiotherapy. Swelling reappeared at same site after 3 months. FNAC of swelling shows large spindle cells having elongated buckled nuclei, pointed end, with varying nucleus size and coarse nuclear chromatin. Few cells are showing Rabdomyoblastic differentiation.